2018
DOI: 10.1111/bju.14197
|View full text |Cite
|
Sign up to set email alerts
|

Repeat prostate‐specific antigen (PSA) test before prostate biopsy: a 20% decrease in PSA values is associated with a reduced risk of cancer and particularly of high‐grade cancer

Abstract: In a cohort of Italian men undergoing prostate biopsy, a reduction of ≥20% in PSA levels significantly reduced the risk of high-grade prostate cancer. Further multicentre studies should validate our present results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Serum PSA is widely used in PCa screening due to its high diagnostic sensitivity and low testing cost (3). However, decades of clinical experience have shown that PSA is not ideal in terms of specificity, often leading to either overdiagnosis or overtreatment (4)(5)(6). Prostate biopsy is the most valuable method in the diagnosis of PCa (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Serum PSA is widely used in PCa screening due to its high diagnostic sensitivity and low testing cost (3). However, decades of clinical experience have shown that PSA is not ideal in terms of specificity, often leading to either overdiagnosis or overtreatment (4)(5)(6). Prostate biopsy is the most valuable method in the diagnosis of PCa (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…After a review of sunny Mediterranean regions, it was concluded that maternal 25-(OH) D <20 ng/mL is very common, with a prevalence rate ranging from 23-90% (22). In Nordic countries, the proportion of vitamin D deficiency among pregnant women at 12 and 20 weeks of pregnancy is up to 96% (23) In summary, the level of 25-(OH)D in pregnant URSA women is significantly lower than that in normal pregnant women. VDR gene Fok I polymorphism may be associated with the occurrence of URSA, and allele F may reduce the risk of URSA.…”
Section: Discussionmentioning
confidence: 99%
“…The serum PSA is an important biomarker that correlates with the risk of PCa ( 13 ). In general, a PSA level of > 4 ng/ml is considered abnormal.…”
Section: Discussionmentioning
confidence: 99%